2017
DOI: 10.1021/acs.est.7b00107
|View full text |Cite
|
Sign up to set email alerts
|

Structures and Properties of As(OH)3 Adsorption Complexes on Hydrated Mackinawite (FeS) Surfaces: A DFT-D2 Study

Abstract: Reactive mineral–water interfaces exert control on the bioavailability of contaminant arsenic species in natural aqueous systems. However, the ability to accurately predict As surface complexation is limited by the lack of molecular-level understanding of As–water–mineral interactions. In the present study, we report the structures and properties of the adsorption complexes of arsenous acid (As(OH)3) on hydrated mackinawite (FeS) surfaces, obtained from density functional theory (DFT) calculations. The fundame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(22 citation statements)
references
References 77 publications
(185 reference statements)
1
20
0
Order By: Relevance
“…The frozen cores of the Fe, O, S and C atoms were defined up to and including the 3p, 1s, 2p and 1s electrons, respectively. Kohn-Sham valence states were expanded in a planewave basis set with a cutoff for the kinetic energy of 400 eV for Fe 3 O 4 [63] and FeS [51,66,69,72,73], and fixed at 600 eV for Fe 3 S 4 [50,52,[74][75][76][77][78][79], in agreement with previous publications. The Brillouin zone integrations of the surface slabs were performed using a Γ-centred Monkhorst-Pack grid of 5 × 5 × 1 k-points for the simulation of all the materials considered.…”
Section: Density Functional Theory Calculations (A) Calculation Detailsmentioning
confidence: 99%
See 2 more Smart Citations
“…The frozen cores of the Fe, O, S and C atoms were defined up to and including the 3p, 1s, 2p and 1s electrons, respectively. Kohn-Sham valence states were expanded in a planewave basis set with a cutoff for the kinetic energy of 400 eV for Fe 3 O 4 [63] and FeS [51,66,69,72,73], and fixed at 600 eV for Fe 3 S 4 [50,52,[74][75][76][77][78][79], in agreement with previous publications. The Brillouin zone integrations of the surface slabs were performed using a Γ-centred Monkhorst-Pack grid of 5 × 5 × 1 k-points for the simulation of all the materials considered.…”
Section: Density Functional Theory Calculations (A) Calculation Detailsmentioning
confidence: 99%
“…The Brillouin zone integrations of the surface slabs were performed using a Γ-centred Monkhorst-Pack grid of 5 × 5 × 1 k-points for the simulation of all the materials considered. A Hubbard Hamiltonian [80] in the version of Dudarev et al [81] was used for the description of the localized and strongly correlated d Fe electrons of the spinel materials, while we found that it is not needed to describe the properties of FeS correctly [51,66,69,72,73,82]. Following previous works, we have chosen U eff = 3.7 eV for Fe 3 O 4 [63] and 1.0 eV for Fe 3 S 4 [50,75,76,83].…”
Section: Density Functional Theory Calculations (A) Calculation Detailsmentioning
confidence: 99%
See 1 more Smart Citation
“…[7,109,110,111,112,113] And the anions required for charge parity in green rust were engaged through ion-dipole interactions with FeIII/FeII cations. [114,115] In strong contrast, nano-confinement of water in mackinawite greatly enhances its self-dissociation, entailing no entropic cost and permits almost frictionless flow between the tetrahedral sheets. [116] Proton flow comparable to that in bulk water in these circumstances would have been via the Grotthuss mechanism at a rate of around 25 nm ns −1 .…”
Section: The Precipitate Mound At the Submarine Alkaline Ventmentioning
confidence: 99%
“…Such information cannot be obtained directly from experiment and the underlying physical driving forces that control the reactivity of hydrazine with the Ni surfaces are therefore still not fully understood. However, electronic structure calculations based on the density functional theory (DFT) [9] provide an alternative way to gain fundamental insight into these processes, as they are capable of accurately predicting lowest-energy adsorption geometries and identifying charge transfer and other electronic effects [10][11][12].…”
Section: Introductionmentioning
confidence: 99%